ABOUT SOME SYMBOLS IN THE TRADITIONAL CLOTHES OF UZBEKS - Ruzmetova Roziyajon (Scholars Digest Publishing, 2025)
This article analyzes the national costumes of the Uzbeks of the Khorezm oasis, their unique aspects, their importance in social life, and the symbols and allusions reflected in national costumes through historical and ethnographic sources.
Keywords: Dresses, сhugurma , belt